Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1055/s-0030-1250523
|View full text |Cite
|
Sign up to set email alerts
|

In VitroGrowth Inhibitory Effects of Cytochalasins and Derivatives in Cancer Cells

Abstract: The in vitro anticancer activity of eight natural cytochalasins and three hemisynthetic derivatives of cytochalasin B on six cancer cell lines was evaluated. The IC (50) in vitro growth inhibitory concentrations, as determined by an MTT colorimetric assay, ranged between 3 and 90 µM and did not relate to the intrinsic sensitivity of the cancer cell lines to proapoptotic stimuli. Structure activity relationship (SAR) analyses revealed that the presence of an unmodified hydroxyl group at C-7 of the perhydroisoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 33 publications
1
44
0
Order By: Relevance
“…More than 60 different cytochalasins from several species of fungi have been classified into various subgroups based on the size of the macrocyclic ring and the substituent of the perhydroisoindolyl-1-one residue at the C-3 position [40]. Despite this diversity, only cytochalasins B and D have been extensively studied for their chemotherapeutic potential.…”
Section: Candidate Migrastatic Drugsmentioning
confidence: 99%
“…More than 60 different cytochalasins from several species of fungi have been classified into various subgroups based on the size of the macrocyclic ring and the substituent of the perhydroisoindolyl-1-one residue at the C-3 position [40]. Despite this diversity, only cytochalasins B and D have been extensively studied for their chemotherapeutic potential.…”
Section: Candidate Migrastatic Drugsmentioning
confidence: 99%
“…These congeners are characterized by a highly substituted perhydro-isoindolone structure that is typically attached to a macrocyclic ring [ 1 ]. More than 60 different cytochalasins from several species of fungi have been classified into various subgroups based on the size of the macrocyclic ring and the substituent of the perhydroisoindolyl-1-one residue at the C-3 position [ 2 ]. However, the most studied congener in regards to antineoplastic activity has been cytochalasin B.…”
Section: Introductionmentioning
confidence: 99%
“…However, the most studied congener in regards to antineoplastic activity has been cytochalasin B. As a microfilament-disrupting agent, cytochalasin B alters cell motility, adherence, secretion, drug efflux, deformability, morphology, and size, among many other effects [ 1 , 2 ]. The effects of cytochalasin B on cell adherence include alteration of cell junctions, leading to changes in tissue physiology and transport.…”
Section: Introductionmentioning
confidence: 99%
“…However, computer-assisted phase-contrast microscopy performed by Van Goietsenoven et al revealed that cytochalasins can be grouped into two categories, i.e., cytotoxic versus cytostatic, indicating that it may be possible to develop novel, non-toxic cytostatic anticancer agents by tuning cytochalasin targets. 27) Our results showed that cytochalasin H isolated from G. sinensis thorns can successfully inhibit the angiogenic properties, such as cell growth, mobility, and 3 dimensional-tube formation (≥125 nmol/L), of HUVEC in vitro, and blood vessel formation by mouse endothelial cells in vivo (≥250 nmol/L) without seriously altering cell viability. The effective doses in our study are relatively low doses when compared with the LD 50 of 12.5 mg/kg that was observed in day-old cockerels.…”
Section: Discussionmentioning
confidence: 66%